Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1093/jn/131.10.3098
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Indigestible Carbohydrates Affect Short-Chain Fatty Acid Formation in the Hindgut of Rats

Abstract: The fermentability and pattern of short-chain fatty acids (SCFA) formed in the hindgut of rats given various combinations of dietary fibers (DF) and resistant starch (RS) were investigated. Highly fermentable indigestible carbohydrates, i.e., guar gum (GG), pectin (Pec) and high amylose cornstarch (HAS), and a DF with a relatively high resistance to fermentation, i.e., wheat bran (WB), were included. The substrates were studied individually or as mixtures (GG + Pec, GG + WB and HAS + WB, 1:1, wt/wt indigestibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
2
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 45 publications
4
71
2
3
Order By: Relevance
“…One may speculate whether a combination with wheat bran will increase the distal and/or faecal concentrations of CAs. Studies in rats have shown that by combining a highly fermentable type of resistant starch with the more resistant wheat bran shifted the fermentation and release of CAs to the distal part of colon (Henningsson et al, 2002).…”
Section: Oat Bran Increases Faecal Cas U Nilsson Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…One may speculate whether a combination with wheat bran will increase the distal and/or faecal concentrations of CAs. Studies in rats have shown that by combining a highly fermentable type of resistant starch with the more resistant wheat bran shifted the fermentation and release of CAs to the distal part of colon (Henningsson et al, 2002).…”
Section: Oat Bran Increases Faecal Cas U Nilsson Et Almentioning
confidence: 99%
“…Different types of indigestible carbohydrates give rise to different amounts and patterns of CAs during colonic fermentation, and it may therefore be possible to regulate the CA formation by diet. The CAs formed may depend on for example the monomeric composition of the carbohydrates, the type of linkages between the carbohydrate monomers, their solubility and their molecular weight (Berggren et al, 1993;Casterline et al, 1997;Bird et al, 2000;Karppinen et al, 2000;Henningsson et al, 2002Henningsson et al, , 2003Nilsson and Nyman, 2005). Studies examining CA formation have mainly been conducted in vitro by using human faecal inocula, or in vivo using animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that fermentable carbohydrates can increase urea flux from the blood to the digestive tract and alter fermentation in the large intestine of rats (Ré mé sy and Demigné, 1989;Younes et al, 1995b;Henningsson et al, 2002). In rabbits, a considerable portion of endogenous urea is transferred to the alimentary tract (Regoeczi et al, 1965), and the exchange between blood urea nitrogen (N) and cecal ammonia N is well established Parker, 1985a and1985b).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the type of indigestible carbohydrate consumed was found to influence the distribution of SCFA in the hindgut of rats (Henningsson et al, 2002) and pigs (Bird et al, 2004).…”
Section: Discussionmentioning
confidence: 89%